Oil and gas, technology and humans assessing the human factors of technological change - Albrechtsen, Eirik.; Besnard, D. (Ashgate, 2013)
"The oil and gas industry is going through a major technological shift. This is particularly true of the Norwegian continental shelf where new work processes are being implemented based on digital infrastructure and information technology. The term Integrated Operations (IO) has been applied to this set of new processes. It is defined by the Centre for Integrated Operations in the Petroleum Industry as 'work processes and technology to make smarter decisions and better execution, enabled by ubiquitous real time data, collaborative techniques and access to multiple expertise'"--Provided by publisher.